Calving Interval of Bali Cows in The instalasi populasi dasar Compare to in balai pembibitan Ternak unggul sapi bali, Bali - Baliarti, Endang; Ismaya, Ismaya; Purnomo, Purnomo (The Animal Husbandry Association of Thailand (AHAT), 2012)
Bali cattle is an indigenous cattle in Indonesia, have a good adaptation capability to hazard condition and very popular with their high fertility. This research was conduct to find out the calving interval (CI) in Istalasi Populasi Dasar (IPD), which is village breeding centres owner by the group of farmers compare to in Pusat Pembibitan Ternak Unggul (BPTU) Sapi Bali, the government breeding centre in Bali Island. Using recording of 136 cows at the IPD and 86 cows at the BPTU Bali cattle were calculated the calving date to the next calving in 2009 to 2011. The result showed that CI cows at the IPD (13.7±1.7 months) tend to longer than at the BPTU Bali cattle (12.0±0.3 months). Because of the different management system, the calving interval at the Istalasi Populasi Dasar have longer calving interval compare to at the Pusat Pembibitan Ternak Unggul Bali Cattle.